2001
DOI: 10.1007/s11745-001-0746-0
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effect of conjugated trienoic fatty acids on mouse tumor and human monocytic leukemia cells

Abstract: The cytotoxicity of fatty acids from seed oils containing conjugated linolenic acids (CLN) was studied. Fatty acids from pomegranate, tung, and catalpa were cytotoxic to human monocytic leukemia cells at concentrations exceeding 5 microM for pomegranate and tung and 10 microM for catalpa, but fatty acids from pot marigold oil had no effect at concentrations ranging up to 163 microM. The main conjugated fatty acids of pomegranate, tung, catalpa, and pot marigold were cis(c)9,trans(t)11,c13-CLN (71.7%), c9,t11,t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
152
1
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 172 publications
(162 citation statements)
references
References 18 publications
(24 reference statements)
6
152
1
3
Order By: Relevance
“…Some of its isomers have proven biological activity (SEÇKIN et al, 2005;SUZUKI et al, 2001;YASUI et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of its isomers have proven biological activity (SEÇKIN et al, 2005;SUZUKI et al, 2001;YASUI et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Some CLnA isomers show cytotoxic effects on tumors, inhibit carcinogenesis, and alter lipid metabolism (DESTAILLATS et al, 2005;SUZUKI et al, 2001;YASUI et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…(17). Also we and other researchers have shown the cytotoxic effect of PGO and tung oil on a variety of human cancer cell lines, including colon cancer cells (18,19).…”
Section: Introductionmentioning
confidence: 61%
“…In addition, our recent studies demonstrated that BMO and PGO suppressed azoxymethane (AOM)-induced colon carcinogenesis in rats (12,22). Regarding catalpa seed oil (CPO), we reported the cytotoxic effect of CPO on SV40-transformed Balb 3T3 A31 and human monocytic leukemia cell lines (18), but there are no in vivo studies on the effect of CPO on carcinogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…CLnA는 필수지방산(n-3)인 리놀렌산(α-linolenic acid, C18:3, cis(c)9, c-12, c-15)의 위치기하학적 이성질체로 공 역화이성체인 공액알파리놀렌산은 모두 탄소수가 18개이 며, conjugated의 이중결합을 갖는 이성체인 지방산의 구조 를 갖는다 (Suzuki et al, 2001). CLnA의 대표적인 isomer 형태인 punicic acid(c9 trans(t)11, c13-CLnA)는 석류 종 자유에 약 80%가 함유되어있다 (Cao et al, 2007) A (NH-SL) : it was synthesized at non-solvent (no n-hexane) system (NH-SL) using 1:6 molar ratio of palm stearin (PS) and HPSO for 72 hr in a shaking water bath set at 65℃ and 185 rpm, B (H-SL) : it was synthesized at solvent (n-hexane) system (H-SL) using 1:6 molar ratio of palm stearin (PS) and HPSO for 72 hr in a shaking water bath set at 65℃ and 185 rpm.…”
unclassified